Ersetzen und Entsühnen : Das Mittelhethitische Ersatzritual für den Großkönig Tuth̬alija (CTH *448.4) und verwandte Texte - Taracha, Piotr (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
A conspicuous hiatus in literature on Hittite ritual exists on the transfer and substitution techniques or motifs. This is the first full description and analysis of this ritual, and as such provides the readers with an important contribution to our understanding of Hittite religious practice. The Hittite substitution ritual is here presented making use of much new textual material. It presents the manuscripts with translations and transcriptions of all duplicate texts, an ample glossary of words, full thematic indices, and commentaries. The latter shed light on the linguistic and cultural aspects, the role of chthonic deities, the cult of ancestors of North Syrian origin, etc., thus also defining a history of various purification motifs in Hittite substitution rituals.